2020
DOI: 10.3390/app10227968
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Devices to Investigate the Long-Term Stability of Phase Change Materials under Application Conditions

Abstract: An important prerequisite to select a reliable phase change material (PCM) for thermal energy storage applications is to test it under application conditions. In the case of solid–liquid PCM, a large amount of thermal energy can be stored and released in a small temperature range around the solid–liquid phase transition. Therefore, to test the long-term stability of solid–liquid PCM, they are subjected to melting and solidification processes taking into account the conditions of the intended application. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
5
0
1
Order By: Relevance
“…For all potential PCMs, knowledge of supercooling is essential, and DSC traces both on melting and freezing should be presented in published work. For most potential PCMs, investigations of long-term thermal cycling using known methodologies [93] are lacking, and such information would significantly advance the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For all potential PCMs, knowledge of supercooling is essential, and DSC traces both on melting and freezing should be presented in published work. For most potential PCMs, investigations of long-term thermal cycling using known methodologies [93] are lacking, and such information would significantly advance the field.…”
Section: Discussionmentioning
confidence: 99%
“…10%) on melting. A thorough study of paraffin PCMs [27] showed no significant variation in ∆ fus H and T fus for paraffins over 3000 meltfreeze cycles, including heating to 90 • C. (The importance of long-term cycling stability for PCMs and experimental devices to quantify this matter have been described recently elsewhere [93]). Furthermore, in that study the paraffins were placed in contact with 17 different materials, including metals, metal alloys, and plastics, at 75 • C for 12 weeks.…”
Section: Other Practical Mattersmentioning
confidence: 95%
“…The fourth paper resulted from the collaboration of several institutions and was developed within the framework of Annex 33/SHC Task 58 Material and Component Development for Compact Thermal Energy Storage, a joint working group of the Energy Storage (ES) and Solar Heating and Cooling (SHC) Technology Collaboration Programmes of the International Energy Agency (IEA) [4]. It consisted of a survey with a detailed description of the experimental devices present in those institutions and used for investigating the long-term stability and performance of PCMs under application conditions [5]. In fact, an important prerequisite to select a reliable material for thermal energy storage applications is to investigate its performance under real working conditions.…”
Section: Advanced Phase Change Materials For Thermal Storagementioning
confidence: 99%
“…Особенно интенсивно исследуются теплоаккумулирующие материалы [9]. В частности, на основе таких органических соединений, как миристиновая, пальмитиновая и стеариновая кислота [10], сложные эфиры и жирные кислоты [11], проводятся исследования и других теплофизических характеристик органических веществ [12][13][14]. Дополнительно в пользу данного метода свидетельствует то, что материалы на основе бензофенона ГСО 11070-2018 и бензойной кислоты ГСО 11071-2018 были охарактеризованы этим же методом.…”
Section: Introductionunclassified